Importance of tyrosine phosphorylation in receptor kinase complexes. (May 2015) - Macho, Alberto P.; Lozano-Durán, Rosa; Zipfel, Cyril
Highlights Components of brassinosteroid and PAMP receptor complexes are phosphorylated on tyrosine residues. Tyrosine phosphorylation is an important mechanism for the activation of receptor kinase complexes. Phosphorylation of specific tyrosine residues could contribute to specific signaling outcomes.